Marine tourism attraction development strategy at Miti Island Tourism Destination, North Halmahera District - Francisca Titing Koernawaty; I Made Sudjana; I Wayan Kiki Sanjaya; Cristallya Eylana Pawane (Institute of Computer Science (IOCS), 2023)
The North Halmahera Regency Government has the responsibility to create the best and most competitive tourist attractions and creative businesses. Miti Island is an unregulated tourist destination and developed as a luxury product. This study proposes two problem formulations. First, what is the potential of the Miti Island Tourism Center that can be developed and developed in northern Halmahera Regency, and second, what is the strategy for developing the Miti Island Tourism Center for seawater tourism. Data collection used interviews and observations to obtain information. It is then processed and classified as component 4A. The purpose of this analysis is to identify tourism resources and development plans for Miti Island as a marine tourism product, as well as make recommendations that can have a positive impact on the health and economy of the people of Miti Island. Data analysis used in this research is descriptive analysis and SWOT analysis. The results of this study identify the tourism potential of Miti Island as a 4A component. This provides tourists with convenient location, accessibility and additional services. The development strategy that can be used for marine tourism on Miti Island is as follows. Miti Island tourism development, economic development environmental development (physical, economic, humanitarian /community)